Gabon's results at the CAMES CCI 2023 ? A wealth of information to improve teaching and research - (:unkn) unknown (My University, 2024)
Making data available (information) for private or public access (e.g. on the Internet) is a lengthy process. Data needs to be created (collection, measurement, sampling), organized (database, files, folders), reduced in size (compression, archiving) and disseminated (emailing, website access). The way in which disseminated data are presented (data history, file type, data formatting) can facilitate or complicate their future exploitation. For various reasons, we decided to study the results file corresponding to teachers and researchers promoted at the 23rd session of the CAMES CCI. In our case, we restricted ourselves to those promoted in Gabon in July 2023. A series of procedures, including simple statistical analyses using pivot tables in MS Excel 2021, enabled us to obtain some results. Significantly more teacher-researchers than researchers were promoted. Assistant professors were the most numerous. Profiles in Humanities and Languages accounted for the lion's share, with 50% of those promoted rated A. Historic establishments were the most successful. Regardless of rank, category, establishment, rating or CTS, women promoted in Gabon generally represented only a third of men. We have attempted to justify the results observed and, above all, to propose remedial actions, in particular those aimed at improving the current presentation of CAMES data.
Keywords: African Research